2015
DOI: 10.1038/modpathol.2014.158
|View full text |Cite
|
Sign up to set email alerts
|

Update for the practicing pathologist: The International Consultation On Urologic Disease-European association of urology consultation on bladder cancer

Abstract: The International Consultations on Urological Diseases are international consensus meetings, supported by the World Health Organization and the Union Internationale Contre le Cancer, which have occurred since 1981. Each consultation has the goal of convening experts to review data and provide evidence-based recommendations to improve practice. In 2012, the selected subject was bladder cancer, a disease which remains a major public health problem with little improvement in many years. The proceedings of the 2nd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 79 publications
(92 reference statements)
1
71
1
2
Order By: Relevance
“…All sections were reviewed by a senior genitourinary pathologist to confirm the original diagnoses according to the WHO/ISUP 2004 classification criteria and the updated 2015 International Consultation on Urologic Diseases (ICUD) recommendations [3]. Specimens with surface and/or invasive micropapillary histology in the bladder and upper urinary tract were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…All sections were reviewed by a senior genitourinary pathologist to confirm the original diagnoses according to the WHO/ISUP 2004 classification criteria and the updated 2015 International Consultation on Urologic Diseases (ICUD) recommendations [3]. Specimens with surface and/or invasive micropapillary histology in the bladder and upper urinary tract were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…4 ), the long debated category by different authors [2][3][4][5][6][7][8][9] . In fact, our study showed Values are expressed as n (%).…”
Section: Discussionmentioning
confidence: 99%
“…Almost 80% of superficial bladder cancers are low grade and low stage and have a non-invasive behaviour 1. Nevertheless, they are characterised by a high recurrence rate, which distinguishes them from other types of bladder cancer.…”
Section: Introductionmentioning
confidence: 99%